2002
DOI: 10.1037/h0086914
|View full text |Cite
|
Sign up to set email alerts
|

The rise of qualitative research in psychology.

Abstract: A study is presented on the rise of qualitative research in psychology over the 20th century. The incidence of qualitative research as indicated by several search terms (i.e., "qualitative research," "grounded theory," "discourse analy*," "empirical phenomenological," and "phenomenological psychology") was traced through the PsycINFO and Dissertation Abstracts International databases. It was found that, with the exception of the search terms having to do with phenomenology, records containing these search term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 18 publications
1
84
0
4
Order By: Relevance
“…Yet, despite evident enthusiasm for qualitative approaches, examinations of published research in psychological journals generally (Rennie, Watson, & Monteiro, 2002) and in journals published by the APA (Kidd, 2002) show slow progress in dissemination of qualitative findings through conventional research outlets. On the basis of a content analysis of journal editorial statements and interviews with editors from 10 APA journals, Kidd (2002) concluded that one barrier to publication of qualitative work in these highly visible journals is precisely their tradition of equating scientific research with quantitative methods and the consequent perceived and actual ambivalence on the part of editors about the potential contribution to knowledge of qualitative scholarship.…”
Section: Evolving Models Of Qualitative Scholarshipmentioning
confidence: 96%
“…Yet, despite evident enthusiasm for qualitative approaches, examinations of published research in psychological journals generally (Rennie, Watson, & Monteiro, 2002) and in journals published by the APA (Kidd, 2002) show slow progress in dissemination of qualitative findings through conventional research outlets. On the basis of a content analysis of journal editorial statements and interviews with editors from 10 APA journals, Kidd (2002) concluded that one barrier to publication of qualitative work in these highly visible journals is precisely their tradition of equating scientific research with quantitative methods and the consequent perceived and actual ambivalence on the part of editors about the potential contribution to knowledge of qualitative scholarship.…”
Section: Evolving Models Of Qualitative Scholarshipmentioning
confidence: 96%
“…In the same way that qualitative approaches in general have grown more quickly in the UK than in some other countries, discourse analysis (DA) is also more common here (Rennie et al, 2002) with many of the key discourse analysts based at centres like Loughborough University, Manchester Metropolitan University and the Open University. Of all qualitative approaches, DA is probably one of the most complex to learn.…”
Section: The Mystifications Of Discourse Analysismentioning
confidence: 99%
“…This conclusion can be further supported by a contradiction that characterizes the status of qualitative research today. On the one hand, even though still peripheral, the frequency of publishing qualitative studies increases in many fields of science, including counseling research (Berrios and Lucca 2006), general medicine (Yamazaki et al 2009), language teaching (Richards 2009), social research (Gwyther and Possamai-Inesedy 2009), and psychology (Rennie et al 2002). At the same time, however, qualitative research is increasingly rejected as non-scientific by major research-funding agencies in different countries, USA (Denzin and Lincoln 2005a;Lather 2004) and Australia (Gwyther and Possamai-Inesedy 2009) among them.…”
Section: Summary Of Problems With the Modern Qualitative Research Metmentioning
confidence: 99%